Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan terhadap Tingkat Pengangguran melalui Belanja Tidak Langsung pada Kabupaten/Kota di Provinsi Bali - Adriani, Ni Luh Gede Cintya; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
The unemployment rate is a problem experienced in each area, including at the district / city in the province of Bali. The rapid development is expected to impact the achievement of a decrease in the unemployment rate. This study aimed to investigate the effect of direct and indirect between local revenues and equalization funds against unemployment through indirect expenditures. This research was conducted in all districts / cities in the province Bali. Data collection is done through the documents contained in the BPS Bali Province. The data used in this research is secondary data, while the method of analysis or path analysis path analysis to determine the direct effect as well as Sobel test to determine the effect is not immediate. The analysis showed that the PAD and the balance funds have positive and significant direct effect on the indirect spending. PAD and fund balance of positive and significant direct effect on the unemployment rate and indirect expenditures and significant negative direct effect on the unemployment rate. PAD through indirect expenditures and fund balance significant indirect effect on the unemployment rate. Langgung not mean spending an intervening variable of PAD and the balance funds.
Keywords: local revenue, equalization funds, indirect expenditure, the unemployment rate